The Relationship between Lipid Profile and Breast Parenchymal Density From Mammography Examination - Yudisthira, Dewangga; Setyawan, Agung; Wadjib, Yuyun Yueniwati Prabowati (International Journal of Radiology and Imaging, 2022)
Breast cancer is a type of cancer that has the highest incidence and mortality rate in the world and in Indonesia among other cancers. One of the causes of death due to breast cancer is influenced by poor prognosis due to cancer’s late detection. One method of early detection is mammography. Mammography is an examination method to detect cancer cells and assess breast density, which is a risk factor for breast cancer. Reporting the results of breast density types uses the BI-RADS grading, which is divided into 4 categories. Breast density is influenced by various factors, one of which is the lipid profile (triglycerides, total cholesterol, LDL, and HDL). This study used an analytic observational method with a cross-sectional study design. The samples were members of Dharma Wanita group of Universitas Brawijaya and female members of the Indonesian Radiographers Association in Malang from October 2021 to January 2022. The data was analyzed using the non-parametric chi-square test. The results of each component of the lipid profile showed p-values (p < 0.05) = 0.172, 0.619, 0.226, 0.829, for triglycerides, total cholesterol, LDL, and HDL, respectively. This means all lipid profile components do not have a significant relationship with the density of the breast parenchyma.